(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article explores effective approaches and methodologies for teaching English to visually impaired students, focusing on adaptive teaching strategies, technological tools, and inclusive educational practices. Through analysis of existing literature, the study examines current best practices and challenges in this specialized field of language education.